Genome-Wide Assessment of Diversity and Divergence Among Extant Galapagos Giant Tortoise Species. (7th July 2018) - Miller, Joshua M; Quinzin, Maud C; Edwards, Danielle L; Eaton, Deren A R; Jensen, Evelyn L; Russello, Michael A; Gibbs, James P; Tapia, Washington; Rueda, Danny; Caccone, Adalgisa
Abstract: Genome-wide assessments allow for fuller characterization of genetic diversity, finer-scale population delineation, and better detection of demographically significant units to guide conservation compared with those based on "traditional" markers. Galapagos giant tortoises ( Chelonoidis spp.) have long provided a case study for how evolutionary genetics may be applied to advance species conservation. Ongoing efforts to bolster tortoise populations, which have declined by 90%, have been informed by analyses of mitochondrial DNA sequence and microsatellite genotypic data, but could benefit from genome-wide markers. Taking this next step, we used double-digest restriction-site associated DNA sequencing to collect genotypic data at >26000 single nucleotide polymorphisms (SNPs) for 117 individuals representing all recognized extant Galapagos giant tortoise species. We then quantified genetic diversity, population structure, and compared results to estimates from mitochondrial DNA and microsatellite loci. Our analyses detected 12 genetic lineages concordant with the 11 named species as well as previously described structure within one species, C. becki . Furthermore, the SNPs provided increased resolution, detecting admixture in 4 individuals. SNP-based estimates of diversity and differentiation were significantly correlated with those derived from nuclear microsatellite loci and mitochondrial DNA sequences. The SNP toolkit presented here will serve as a resource for advancing efforts to understand tortoise evolution, species radiations, and aid conservation of the Galapagos tortoise species complex.